Resistance Performance Forecast of Trimaran Based on Multiple Regression Analysis - Xu Xiao Ying; Meng Chao Ying; Wang Kuan (E3S Web of Conferences, 2021)
Based on the multiple linear regression of the relevant data of 29 ships in the basic database, including cargo ship, oil ship, container ship and chemical ship, etc, the empirical estimation formula of resistance coefficient of single ship under different Fr was obtained. The feasibility of applying the above regression formula to the prediction of the resistance performance of the trimaran based on DTMB5415 is verified by comparison with CFD simulation data. This method has a strong engineering applicability and provides a new idea for the study of computer-aided layout optimization of the trimaran.